2016
DOI: 10.1007/s00170-016-8667-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of process parameters on kerf geometry and surface roughness in Nd:YAG laser cutting of Al 6061T6 alloy sheet

Abstract: In the present study, fine laser cutting of aluminium alloy 6061-T6 sheets, characterised by light reflection and heat conductivity, by means of a 150-W multimode lamp pumped Nd:YAG laser is investigated through an experimental testing campaign. Design of experiments (DoE) and analysis of variance (ANOVA) are adopted to study the influence of the process parameters on the kerf geometry and surface roughness. The results show that the laser allows cutting 1-mm-thick AA6061-T6 sheets with a cutting speed up to 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Since thermal conductivity refers to the rate at which heat is removed from the cutting area, low thermal resistance increases heat dissipation, resulting in lower energy available to the machining and, consequently, higher energy consumption and loss of efficiency. Moreover, heat removal may result in cooling of the molten metal on the underside of the kerf, tapered edge and slag formation [18]. Furthermore, light reflective metals, such as aluminum alloys, may reduce the maximum cutting speed and require more power density to initiate the cut [5].…”
Section: Methodsmentioning
confidence: 99%
“…Since thermal conductivity refers to the rate at which heat is removed from the cutting area, low thermal resistance increases heat dissipation, resulting in lower energy available to the machining and, consequently, higher energy consumption and loss of efficiency. Moreover, heat removal may result in cooling of the molten metal on the underside of the kerf, tapered edge and slag formation [18]. Furthermore, light reflective metals, such as aluminum alloys, may reduce the maximum cutting speed and require more power density to initiate the cut [5].…”
Section: Methodsmentioning
confidence: 99%
“…Tadavani et al [14] reported that the laser cutting of the Inconel 718b superalloy improved the surface quality by 22%, in comparison to conventional machining. The interdependences between the Nd:YAG laser cutting control factors and the surface roughness and kerf geometry were investigated for the alloy Al 6061T6 [15]. The same responses were also analyzed for the pulsed CO 2 laser cutting in processing the composite material Al6061/Al2O3 [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, an increase of the absorbed energy by heat diffusion into the surrounding area of the worked material occurs, according to what observed in Refs. . The effect of the hatch distance is similar; when the Hd decreases, an increase of the released energy per unit area occurs; thus, Pd increases.…”
Section: Resultsmentioning
confidence: 83%